Tourism Sector Development Through Dynamic Location Quotient and Shift Share Analysis: Pengembangan Sektor Pariwisata Melalui Analisis Dynamic Location Quotient dan Shift Share - Rizky, Indah Mutiara; Imsar, Imsar; Harahap, Muhammad Ikhsan (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Economic disparities between regions in Indonesia remain a persistent development challenge. Specific Background: Langkat Regency, situated within North Sumatra Province, reflects a localized case of uneven growth requiring focused assessment. Knowledge Gap: Limited studies have examined sector-specific contributions, particularly the